Design of a Web-Based Scheduling Information System Using the Codeigniter Framework at the Regional House of Representatives (DPRD) of West Java Provience - Saniati, Saniati; Kusumadiarti, Rini Suwartika; Sufyana, Candra Mecca (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2025)
Information technology today is highly advanced and has a significant impact on the government sector, particularly in managing time and resources. One application of information technology is the scheduling information system for the members of the West Java Provincial DPRD. However, until now, the scheduling system in the West Java Provincial DPRD still uses a manual method with Microsoft Word. This has resulted in the scheduling process being less efficient and highly prone to errors. The manual method complicates data retrieval, information updates, and structured documentation. To address this issue, a web-based scheduling information system has been designed using the CodeIgniter framework. The development method used is the waterfall method, which starts from the requirements analysis phase to the maintenance phase. System testing is conducted using the black-box method and questionnaires, which indicate that all functions within the system operate well according to user needs. With this information system, the scheduling process in the West Java Provincial DPRD becomes faster, more accurate, and well-documented. This system also assists staff in organizing and monitoring activity schedules, while reducing errors that often occur in the manual system.